2017
DOI: 10.1002/14651858.cd006887.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Risk scoring for the primary prevention of cardiovascular disease

Abstract: There is uncertainty whether current strategies for providing CVD risk scores affect CVD events. Providing CVD risk scores may slightly reduce CVD risk factor levels and may increase preventive medication prescribing in higher-risk people without evidence of harm. There were multiple study limitations in the identified studies and substantial heterogeneity in the interventions, outcomes, and analyses, so readers should interpret results with caution. New models for implementing and evaluating CVD risk scores i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 167 publications
1
102
0
7
Order By: Relevance
“…4,5 Risk prediction models can be a component of cardiovascular disease prevention and control efforts, because they can help to identify people at high risk of cardiovascular disease who should benefit the most from preventive interventions. 6,7 Many such risk prediction models have been developed, [8][9][10][11][12][13] usually estimating individual risk over a 10-year period by use of measured levels of conventional risk factors for cardiovascular disease. 14 However, available models have limitations for use in low-income and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Risk prediction models can be a component of cardiovascular disease prevention and control efforts, because they can help to identify people at high risk of cardiovascular disease who should benefit the most from preventive interventions. 6,7 Many such risk prediction models have been developed, [8][9][10][11][12][13] usually estimating individual risk over a 10-year period by use of measured levels of conventional risk factors for cardiovascular disease. 14 However, available models have limitations for use in low-income and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, we recently completed a systematic review that identified multiple evidence gaps pertaining to the best strategies for implementing these risk estimates in clinical practice (Karmali et al, 2017). One commonly cited limitation in prior studies was missing or incomplete risk factor data at the time of a clinical encounter.…”
Section: Discussionmentioning
confidence: 99%
“…Confirming of the utility of preventive approaches in midlife, a recent Cochrane review including 41 randomized controlled trials totalling 194,035 participants showed that providing cardiovascular risk scores reduced total cholesterol and systolic blood pressure as compared with usual care 44 . Moreover, providing cardiovascular risk scores may increase preventive medication prescribing (lipid-lowering therapy and antihypertensive drugs) in highrisk groups 44 . It is therefore logical to imagine that better cardiovascular treatment could limit cardiovascular events and their functional consequences.…”
Section: • Midlife Prevention Of Non-communicable Diseases and Age-rementioning
confidence: 99%